The Effect of Therapy Intervention of Group Activity Socialization (Taks) on the Social Interaction Abilities of Children and Adolescents - Supriyadi Supriyadi; Siswani Mariana; Agung Setiyadi; Aliana Dewi; Yulinda Yulinda (Indonesian Journal of Global Health Research, 2026)
Mental disorders are conditions that affect a person's thoughts, feelings, and behavior, thus disrupting social functioning, work, and family relationships. One of the surgical interventions used to treat clients with similar problems is Group Activity Therapy (GAT). Its forms include socialization GAT, which is a therapy that aims to improve social skills through structured group activities and facilitated by health professionals. This therapy focuses on improving communication skills, empathy, and cooperation between individuals. This study aims to determine the effect of the socialization GAT intervention on the social interaction skills of children and adolescents with social isolation. The research method used a quasi-experimental design with a one-group pre-test and post-test. A total of 30 respondents aged 9–19 years diagnosed with social isolation were selected using a total sampling technique. The intervention was carried out for seven sessions, and social interaction skills were measured before and after the intervention using an observation sheet. Data analysis used the Kolmogorov-Smirnov normality test and Paired Sample t-Test. The results showed that before the intervention, 86.7% of respondents were in the "sufficient" category, while after the intervention, this increased to 50% "good" and 50% "very good". Statistical testing showed a p-value of 0.001 (p < 0.05), indicating a significant effect of TAK socialization on improving social interaction skills. In conclusion, TAK socialization is effective in improving social interaction in children and adolescents with social isolation and is suitable for continued implementation in psychiatric care.